2023
DOI: 10.1111/cns.14265
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid as a therapeutic agent in depression: Evidence from preclinical studies

Abstract: Depression is a common but severe mood disorder with a very high prevalence across the general population. Depression is of global concern and poses a threat to human physical and mental health. Ferulic acid (FA) is a natural active ingredient that has antioxidative, anti‐inflammatory, and free radical scavenging properties. Furthermore, studies have shown that FA can exert antidepressant effects through a variety of mechanisms. The aim of the review was to comprehensively elucidate the mechanisms in FA that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 112 publications
0
4
0
Order By: Relevance
“…According to clinical research, stress triggers the activation of microglia, leading to a rise in the production of pro-inflammatory cytokines. However, it has been found that Ferulic acid could block the excitation of microglia and reduce the levels of pro-inflammatory cytokines [ 30 , 31 , 32 , 33 ]. Moreover, Z-ligustilide exhibits substantial potential in the areas of antidepression and the regulation of gut flora, among other aspects [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to clinical research, stress triggers the activation of microglia, leading to a rise in the production of pro-inflammatory cytokines. However, it has been found that Ferulic acid could block the excitation of microglia and reduce the levels of pro-inflammatory cytokines [ 30 , 31 , 32 , 33 ]. Moreover, Z-ligustilide exhibits substantial potential in the areas of antidepression and the regulation of gut flora, among other aspects [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has the advantage of a rapid onset of action and exerts a significant antidepressant effect by modulating multiple neurotransmitters, including dopamine, GABA, and norepinephrine [ 66 , 67 ]. In addition, we also screened some natural products from plants such as ferulic acid and isochlorogenic acid B. Ferulic acid has been proven to produce significant antidepressant effects in animal models of MDD through various mechanisms, providing a solid basis for its clinical application [ 68 ]. Ferulic acid can significantly improve APP deposition-induced neurofunctional impairments by activating the PI3K/Akt signaling pathway [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…FA can achieve significant alleviation of depression in animal models by enhancing monoamine oxidase A (MOA) activity, promoting hippocampal nerve regeneration, anti-oxidative stress, and anti-inflammatory activity, and activating the protein kinase B/collapsin response mediator protein 2 (AKT/CRMP2) signalling pathway. 52…”
Section: Biological Activitiesmentioning
confidence: 99%